(In)Congruence of Implicit and Explicit Communal Motives Predicts the Quality and Stability of Couple Relationships. Issue 4 (21st February 2013) - Hagemeyer, Birk; Neberich, Wiebke; Asendorpf, Jens B.; Neyer, Franz J.
Abstract: Objective: Previous research has shown that motive congruence, as observed in convergingly high or low scores on implicit and explicit motive measures, promotes well‐being and health. Extending this individual perspective to the realm of couple relationships, the present investigation examined intra‐ and interpersonal effects of communal motive (in)congruence on relationship satisfaction and stability. Method: The implicit partner‐related need for communion, the explicit desire for closeness, and relationship satisfaction were assessed in a sample of 547 heterosexual couples aged 18 to 73 years. In a one‐year follow‐up study, information on relationship stability was obtained, and relationship satisfaction was reassessed. The researchers tested cross‐sectional and longitudinal effects of motive (in)congruence by dyadic moderation analyses. Results: Individuals scoring congruently high on both motives reported the highest relationship satisfaction in concurrence with motive assessment and 1 year later. In addition, motive incongruence predicted an increased risk of relationship breakup over 1 year. Conclusions: The results highlight the significance of both implicit and explicit motives for couple relationships. Motive incongruence was confirmed as a dispositional risk factor that so far has not been considered in couple research. Future research directions addressing potential mediators of the observed effects and potential moderators of motive (in)congruence are discussed.